ORIENTALISME DAN IMPLIKASI KEPADA DUNIA ISLAM - Saifullah Isri (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
Orientalism is repercussion of crusade which purposed to against Islam, because of crusade never being stopped. Even Though, the crusade showed the various forms and colors, such as the orientalist. Orientalist appears as the scientist in doing of the research and survey about something on science in intending to propogate any slander and issue; giving full rein of hatred and envy to Islam. The orientalist tries to against Islam and disturb the islamic missionary. It happened because they can not remove theirselves from passion effect to against Islam. Their effort not only in concealing to spread the hesitancy to islamic sources, include the evil in islamic law, direct the moslem in deviate thinking, and attack the arabic language (al-Quran language), but also in declaring the issues to help the propaganda which covered under islamic name.